Formulation of lotion ethanolic extract of rosella flower petals (Hibiscus sabrariffa L.) and antioxidant activity - Fadli, Justitia Cahyani; Lasanudin, Rindi Ibrahim (Journal of Halal Science and Research, 2024)
Rosella flowers (Hibiscus sabrariffa L.) are plants that are useful as antioxidants. The content that acts as an antioxidant is a flavonoid compound. This study aimed to determine the effect of giving calliandra honey as a multiple active ingredient and single active ingredient (rosella petal extract, calliandra honey )  and ethyl vitamin C as an active ingredient. The lotion of ethanolic extract of rosela flower petals was made with three active ingredients: ethanolic extract of roselle flower petals with a concentration of 2.5%, calliandra honey 2.5%, and ethyl vitamin C 2%. Then, calliandra honey and ethanol extract of roselle flowers are combined with a concentration of extract 2.5% and calliandra honey (1.5%, 2%, and 2.5%). The physical and stability tests are the organoleptic, homogeneity, viscosity, dispersibility, pH, lotion stability, and the value of lotion's antioxidant activity. The activity test was carried out using the 2,2-Diphenyl-1-Picryhidrazil (DPPH) method, and the IC50 of inhibition was calculated. The results of the study showed that all lotion formulations had antioxidant activity. The highest antioxidant activity was obtained in formula three, which had a value of 95.2 ppm (2.5: 2.5 %). Based on the Kruskal Wallis test, the asymp value was obtained. Sig. 0.000, which indicates that there is a significant difference in antioxidant activity. This is because the percent inhibition of each sample has a large enough difference.